1988
DOI: 10.1193/1.1585498
|View full text |Cite
|
Sign up to set email alerts
|

The Mexico Earthquake of September 19, 1985—Relationships between Soil Conditions and Earthquake Ground Motions

Abstract: Comparisons are presented between the characteristics of ground motions at five sites underlain by clay at which ground motions were recorded in Mexico City in the earthquake of September 16, 1985 and for which analyses of ground response have been made, based on the measured properties of soils and the motions recorded on hard formations at the National University of Mexico. It is shown that the ground response in areas of Mexico City underlain by clay is extremely sensitive to small changes in the shear wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(86 citation statements)
references
References 0 publications
0
84
0
2
Order By: Relevance
“…In Mexico City in 1985, the maximum rock acceleration was amplified four times by a soft clay deposit that would have been classified as S whereas the spectral amplitudes were 4 about 15 to 20 times larger than on rock at a period near 2 sec. In other parts of the valley where the clay is thicker, the spectral amplitudes at periods ranging between 3 and 4 sec also were amplified about 15 times, but the damage was less due to the low rock motion intensity at these very long periods (Seed et al, 1988). Inspection of the records obtained at some soft clay sites during the 1989 Loma Prieta earthquake indicates a maximum amplification of long-period spectral amplitudes of the order of three to six times.…”
Section: Response Of Soft Sites To Low Rock Accelerationsmentioning
confidence: 99%
“…In Mexico City in 1985, the maximum rock acceleration was amplified four times by a soft clay deposit that would have been classified as S whereas the spectral amplitudes were 4 about 15 to 20 times larger than on rock at a period near 2 sec. In other parts of the valley where the clay is thicker, the spectral amplitudes at periods ranging between 3 and 4 sec also were amplified about 15 times, but the damage was less due to the low rock motion intensity at these very long periods (Seed et al, 1988). Inspection of the records obtained at some soft clay sites during the 1989 Loma Prieta earthquake indicates a maximum amplification of long-period spectral amplitudes of the order of three to six times.…”
Section: Response Of Soft Sites To Low Rock Accelerationsmentioning
confidence: 99%
“…Borcherdt et al, 1979;Joyner et al, 1981;Seed et al, 1988). Williams et al (1999) showed that significant resonances can occur for impedance boundaries as shallow as 7-m depth.…”
Section: Seismic Wave Propagation Amplitude and Phase Factorsmentioning
confidence: 99%
“…Layer resonances and near-surface impedance gradients are the main factors that cause soil amplification in a simple horizontally layered structure (Haskell 1960;Murphy et al 1971;Shearer and Orcutt 1987). The importance of soil amplification has clearly been demonstrated for the Mexico earthquake of 19 September 1985 by Seed et al (1988). Significant damage during the 17 October 1989 Loma Prieta (California) earthquake occurred in areas of San Francisco and Oakland underlain by poor soil Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear characteristic of the soil is usually called dynamic deformation characteristic. Seed and Idriss (1970) and Hardin and Drenevich (1972a, b) expressed nonlinear characteristic of soil is caused by cyclic loading. Thus, earthquake response analysis widely done on computer code SHAKE (Schnabel et al 1972), which based on multiple reflection theory and nonlinearity of soil behavior, considered as equivalent linear method where the stress-strain relationship must be linear in solving the equation of motion in frequency domain.…”
Section: Dynamic Soil Response Analysismentioning
confidence: 99%